Analysis of Spam Transaction on the Blockchain - Kyung Kim, Tae; ., .; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The blockchain has been applied to many fields. Users are concerned about its security. The primary goal of this study is supporting the security service to protect DDoS attack.Methods/Statistical analysis: To provide security service in the blockchain, the security model is suggested. This model can filter out illegitimate traffic and exchange information with other security switches to determine whether a connected node is a normal node or an abnormal node. Each procedure of the proposed model has been described. Also, two different attack types are used to show the operation process of suggested model.Findings: Cyberattacks attempting to impact technology services availability continue to increase. Thus, DDoS is one of the most common type of attacks can also cause the most disruption to internet services. But blockchain has the characteristics of decentralization and peer to peer. This makes it harder to disrupt than conventional distributed application. Nevertheless, DDoS attacks remain a persistent threat. Therefore, a security model is suggested which can effectively block and respond to DDoS attacks.Improvements/Applications: The suggested model makes it possible to protect the spam transaction attacks in blockchain network.Â Â